Experimental Research Progress of mPGES-1 Inhibitor 2,5-dimethylcelecoxib in Various Diseases - Chen, Zhanfei; Chen, Rong; Wang, Laiping; Yu, Zihao; Chen, Weitong; Lin, Hua; Yu, Liumin; Li, Jinqiu; Chen, Zhonghui; Shen, Jianlin; Tang, Nanhong (Current Medicinal Chemistry, 2026)
Prostaglandin E2 (PGE2) plays a crucial role in inflammation. Non-steroidal anti-inflammatory medications are commonly utilized to alleviate pain and address inflammation by blocking the production of PGE2 and cyclooxygenase (COX). However, selective inhibition of COX can easily lead to a series of risks for cardiovascular diseases. Hence, it is imperative to discover safer and more efficient targets for reducing inflammation. Research has demonstrated that mPGES-1 serves as the final enzyme that controls the rate of prostaglandin E2 synthesis. Moreover, it is only triggered by inflammation and could serve as a possible treatment target instead of COX in cases of inflammation. 2,5-dimethylcelecoxib (DMC) can effectively inhibit mPGES-1 expression, maintain the overall balance of prostaglandins, reduce the secretion of PGE2, and, most importantly, avoid the side effects of COX inhibitors. DMC has the ability to address illnesses through the stimulation of autophagy and apoptosis, as well as the regulation of the immune microenvironment and intestinal flora. This study provides a comprehensive overview of the advancements in DMC within experimental research and offers suggestions for potential avenues of future investigation.
Keywords: dimethylcelecoxib